2017
DOI: 10.1111/jfb.13456
|View full text |Cite
|
Sign up to set email alerts
|

Records of ocean sunfish Mola mola along the Norwegian coast spanning two centuries, 1801–2015

Abstract: Records of the ocean sunfish Mola mola along the Norwegian coast were compiled from all possible sources: literature, media, databases and museums. A total of 216 records were found between 1801 and 2015. They were distributed along the whole coast, except for the most north-eastern part. Nearly all years with more than five records were after 2000, with 1985 as the only exception and with a maximum of 23 records in 2014. Most, 92·4%, were from July to December. Records from before 1979 were more incidental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Likewise, sunfish (reported as M. mola) occurring along the coast of Norway likely represents a northern range extension through "intentional, incidental or accidental" northwards movements, associated with the warm waters of the North Atlantic Drift and Norwegian Coastal Current (Frafjord et al 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Likewise, sunfish (reported as M. mola) occurring along the coast of Norway likely represents a northern range extension through "intentional, incidental or accidental" northwards movements, associated with the warm waters of the North Atlantic Drift and Norwegian Coastal Current (Frafjord et al 2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, including very large M. alexandrini in length–weight relationships for other molids will likely cloud length–weight relationships and scaling assessments. Several length–weight relationships have been proposed for M. mola (Frafjord et al ., 2017; Lee et al ., 2013; McClain et al ., 2015; Nakatsubo et al ., 2007a; Watanabe & Sato, 2008) and Mola spp. (Phillips et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in agreement with observations from further north in the North East Atlantic (NEA) where increases in sunfish sightings have been documented. For example, in Icelandic waters, Palsson and Astthorsson (2017) recorded an increase in the occurrence of sunfish since the 2000s and Frafjord et al (2017) reported that annual records of more than five sunfish in Norwegian waters all occurred after 2000. Such observations were reported as evidence of a range expansion for ocean sunfish.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of any long-term fisheries capture (or bycatch data) in the NEA for ocean sunfish, reconstruction of their past trends in abundance must rely on sightings records, which are collected opportunistically (Palsson and Astthorsson 2017;Frafjord et al 2017) or as part of monitoring surveys for other species and through citizen science initiatives. However, such data are more prone to sources of imprecision and bias than data collected through rigorous scientific surveys (Bird et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation